A SEMANTIC ANALYSIS ON ANGEL BABY SONG LYRIC BY TROYE SIVAN - Lariba, Andreas; Oroh, Elisabeth Z.; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research focuses on identifying and finding out the types of meaning behind the text in Angel Baby Song Lyric by Troye Sivan. This research applied semantic approach, a study of the word meaning and sentence meaning as one field branch of linguistics. The researcher has analyzed 13 selected data as samples of meaning from Angel Baby song lyric by Troye Sivan. To analyze this research, descriptive qualitative research was used. From data analyzed, Angel Baby song lyric has six categories types of meaning according to its lyrics; there are 9 conceptual meaning; 3 connotation meaning; 2 reflective meaning; 2 associative meaning; 5 social and emotion meaning; and 6 thematic meaning, therefore the total types of meanings found behind the text of Angel Baby song lyric is 27 data. Conceptual meaning is more dominant than the other stanzas meaning. This song offers a comprehensive emotional psychological insight, highlighting the impact of loss on one's life. It emphasize deep love, intense emotional attachment, and obsession. The song also implicated relationship emotional conflict, showing the dynamics of reconciling competing emotions. The research featured how language evolves not only within the context of books and texts but also through song lyrics, making it easier for language enthusiasts to understood the meaning of language through music.